Rise of Maoism in Nepal: Causes and Consequences - Pariyar, Anita Kumari (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: The growth of Maoism in Nepal is a notable event in Nepal’s socio-political history. It can be attributed to structural inequality, political instability, and ideologization. While there exists abundant literature in regard to the subject matter under consideration, previous studies appear to be limited by their narrow focus on the aspects of politics, economics, and social sciences. Methods: In this paper, the researcher adopted an empirical and conceptual research design relying exclusively on secondary data. A comprehensive literature review of peer-reviewed books, journal articles, and reliable reports was undertaken using theories of political sociology, Marxism, conflicts, and post-conflict development. Results: It has been demonstrated that the Maoist rebellion in Nepal was driven by socio-economic inequality, landlessness, unemployment, and social marginalization combined with political instability and poor governance. Meanwhile, ideology operated as a unifying and justificatory factor. As for the social and economic impact of the rebellion, they entailed mass displacement, mental problems among citizens, destruction of infrastructural facilities, and interference with development initiatives. In turn, the post-conflict period brought substantial political change, which comprised the abdication of the monarchy and formation of the federal democratic republic as well as inclusion of marginalized population groups. Conclusion: Maoism in Nepal demonstrates the intricate relationship between the structural, political, and ideological determinants that influence insurgencies. Peace and development can only be achieved through the application of a holistic approach that not only tackles immediate concerns but also structural inequalities, focusing on good governance and resource management. Originality: This research provides an innovative contribution to the field with its unique methodology of incorporating social, economic, political, and ideological perspectives to give a thorough analysis of the reasons, outcomes, and post-insurgency evolution of Maoism in Nepal, which is hardly ever done in one study explicitly.